Nephroprotective Effect of Green Synthesised Gold Nanoparticles Using Bark Extract of Terminalia arjuna on Acetaminophen Induced Nephrotoxicity in Male Albino Rat: Pharmaceutical Science-Nanotechnology for Better Drug Targeting - Mousumi Mitra; Amit Bandyopadhyay; Gouriprasad Datta; Dilip K Nandi (International Journal of Life Science and Pharma Research, 2022)
Green synthesised gold nanoparticles offer a great promise in biomedicine. An overdose of acetaminophen causes severe hepatotoxicity and nephrotoxicity. The development of nephroprotective drugs through eco-friendly production routes is a major challenge for current pharmacology. This study was undertaken to examine the therapeutic effects of green synthesised gold nanoparticles (AuNPs) using aqueous bark extract of Terminalia arjuna, on acetaminophen induced nephrotoxicity in male albino rats and also to select the most effective dose of AuNPs to protect from nephrotoxicity . Terminalia arjuna , is a herbal plant of high interest in Asian traditional medicine. The bark of this tree has been widely used in the preparation of ayurvedic formulations such as powerful cardiotonic, antioxidative, antiuremic and antimicrobial properties. In this study 36 experimental albino rats were taken and randomly divided into 6 groups. Group 1 served as normal control, Group 2 received acetaminophen intraperitoneally at concentration of 500mg /kg of body weight for 14 days and Groups 3,4,5,6 were co-administered with acetaminophen (500mg/kg/day) along with AuNPs at doses 55, 175, 550, 2000 µg/kg/day intraperitoneally for 14 days. After 14 days all animals were sacrificed for biochemical and histopathological studies. Among different experimental doses of AuNPs (55,175,550, 2000µg/kg/day), 175µg/kg/day showed more potent activity towards biochemical indices and histopathological studies. There was significant (p<0.05) increase in Urea, Creatinine, CRP and MDA levels but significant decrease in SOD, CAT and GSH activity in acetaminophen treated group, in comparison to control group but co-administration with AuNPs (175µg/kg/day) restored the activities of these biochemical markers and also of the antioxidant enzymes. Hence,this study confirmed that AuNPs at dose 175µg/kg/day have better nephroprotective efficacy.